Inovasi Wakaf Digital Sebagai Alternatif Pembiyaan MikroSyariah di Era Ekonomi Digital - aisyah, sukma; Siti Arpah Lubis; Suaidah; Wahyuni Daulay (Badan Wakaf Indonesia, 2025)
Digital waqf innovation as an alternative to sharia microfinancing in the digital economy era shows great potential in increasing community participation and transparency in the management of waqf funds. This research analyzes the role of digital technology in simplifying the process of collecting, managing and distributing waqf funds, as well as its impact on economic empowerment, especially for micro, small and medium enterprises (MSMEs). By using the systematic literature review (SLR) method, this research identifies the challenges faced, such as low digital literacy and uneven infrastructure. The research results show that digital waqf not only functions as an instrument of worship, but also as a strategic tool to create a more just and sustainable economy. Therefore, collaboration between the government, sharia financial institutions and the community is very important to optimize the implementation of digital waqf in a sustainable manner.